Improving work allocation practices in business processes supported by BPMS - Uahi, Robbie (2018)
BPMS (Business Process Management Systems) are responsible for the execution of business process models, by delivering work activities to suitable agents (human or automatisms) that execute them. During the design-time, modelers have to specify the potential performers of a work activity according to their organizational position or role. Once several workers may share the same role, during run-time all of them can be assigned by BPMS to execute a work activity. However, distinct persons have different personality traits and, in a specific piece of work (for instance, requiring special teamwork skills), some of them can perform better than others. Addressing a gap in theory and practice of BPMS, in this paper we present a new approach that enables BPMS to assign (in run-time) the most suitable workers to perform specific work activities, grounded on the concept of psychological profile and taking into account technical, human and social aspects.